THE MIDDLE EOCENE BONY FISH FAUNA OF CALIFORNIA, USA, RECONSTRUCTED BY MEANS OF OTOLITHS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2024)
Large and diverse Eocene otolith assemblages have been described from the US Gulf and Atlantic coastal plains, various basins in Europe, and New Zealand. Here we described a highly diverse otolith association from the middle Eocene (Lutetian and Bartonian) strata of southern California, San Diego County, which was retrieved from the heritage of John E. Fitch (1918-1982) in the archives of the Ichthyology Department of the Natural History Museum of Los Angeles County, Los Angeles, Califronia. The collection represents the first Eocene otolith assemblage described from the Northeastern Pacific and stems from two localities: the Ardath Shale at Black’s Beach in the Torrey Pines Park just south of Black’s Canyon Road and north of the Salk Fault on the Pacific shore face, and the MissionValley Formation from the west-facing graded hill just east of the Miramar Water Treatment Plant near the southern shore of Miramar Reservoir. The Ardath Shale was deposited on the deep shelf and continental slope while the Mission Valley Formation represent an inland, nearshore environment during times of the maximum transgression.            A total of more than15,000 otoliths were found representing 96 species of which 53 are described as new and 12 remain in open nomenclature. The fauna of the Ardath Shale is distinctly richer containing 88 species while the one from the Miramar Reservoir site yielded 38 species. The low diversity at the Miramar Reservoir site is thought to be related to the shallow-water environment in which it was deposited whereas the high diversity at Black’s Beach reflects a mixture of shelf and bathyal fishes. In addition, 24 new otolith-based genera are established, four of which are in the category “incertae sedis”. Furthermore, five new species are described from a comparative otolith collection from the US Gulf Coast Eocene and one new species from a comparative collection from the Lutetian of Balegem in Belgium.            The Eocene otolith-based fish fauna from California is assessed for its paleoecological, paleobiogeographic and evolutionary significance. Particular emphasis is directed towards the elucidation of the evolution of the early Ophidiiformes, which during the early Paleogene were predominantly adapted to warm, clastic shallow-water environments and there were competing in abundance and diversity with other percomorphs (e.g., perciforms s.l.). A warm Eocene paleobioprovince is proposed for the Californian fish fauna which is not related to today’s endemic Northwest Pacific fish fauna along the regime of the cold-water California Current.